Hubungan Karakteristik dengan Anemia Remaja di Daerah Pesisir - Sucita Efendi; Agus Supinganto; Baiq Nurul Hidayati (Journal of Pharmaceutical and Health Research, 2022)
As a result of the growth and development that occurs in adolescence, there can be changes in the types of living habits and consumption behaviors of adolescents. The pattern of low daily iron consumption by young women can make daily iron intake less fulfilling. This study was to determine the relationship between maternal education factors, parental income, nutritional status, knowledge, attitudes, and menstrual patterns with the incidence of anemia in adolescents in the coastal village of Malacca, North Lombok. This type of research is an analytic survey with a cross-sectional approach. The sampling technique was purposive sampling with a sample of 52 people. Data analysis used the chi-square test. There is a relationship between nutritional status and knowledge of adolescents and the incidence of anemia, but there is no relationship between a mother's education, her parents' income, the attitude of adolescents, or menstruation. Improving health promotion through the participation of youth and schools by strengthening the School Health Business program